Comparison between Otoliths and Length Based Ageing and Growth of African Armoured Searobin (Peristedion cataphractum L. 1758; Teleostei, Peristediidae) off the Southern Coasts of Sicily (Mediterranean Sea). (30th September 2015) - Bottari, Teresa; Gancitano, Salvatore; Rinelli, Paola; Ragonese, Sergio
Abstract : The recovering of Peristedion cataphractum otoliths collected between 1991 and 1992 from specimens sampled off the southern coasts of Sicily has allowed a direct ageing and growth estimation to be compared with the length based method estimates produced in successive years. Overall, 855 left otoliths ( sagittae ) were recovered, measured, and read as a whole surface. The core and rings distances were also measured to perform back-calculation. The otolith length-body length relationships were allometric. Back-calculated lengths at age were in agreement with the lengths estimated with otolith readings. Present results showed a good congruency between otoliths and length based method.